PENGARUH STATUS GIZI DAN AKTIFITAS BERMAIN TERHADAP KEMAMPUAN MOTORIK SISWA DISABILITAS (TUNARUNGU) DI SLB NEGERI 2 PADANG - Julinanda, Irvan; Gusril; Susanto, wilda welis; Susanto, Liza (Jurnal IKEOR, 2023)
The absence of motor skills in SLB Negeri 2 Padang pupils was noted as an issue in this study. The independent variable, which covers dietary habits and recreational activities, and the dependent variable, which assesses motor abilities, are used in this study. The purpose of this study is to determine the impact of nutritional status and recreational activities on students' motor abilities at SLB Negeri 2 Padang. This is explanatory research, which seeks to evaluate the link between factors that have previously been theorized. In this study, a hypothesis will be investigated to see if it is true. The population of interest in this study is all students in grades I - XII at SLB 2 Padang during the 2023/2024 academic year, a total of 18 persons. The research sample was selected at appointed (purposive sampling) and included 11 students from grades I-VI. Motor ability tests were employed to acquire study data. The acquired data was then evaluated using the T and F tests.The data analysis results suggest that there is an 81.7% significant relationship between nutritional status and group activities on students' motor abilities, with a significance value (sig) of 0.01, which is less than 0.05. This This suggests states that the alternative hypothesis which states "there is a positive and significant influence between nutritional status and play activities together on students' motor skills at SLB Negeri 2 Padang" is acceptable.